Applied equine nutrition and training : Equine nUtrition and training conference (ENUTRACO) 2011 - Lindner, Arno (Wageningen Academic Publishers, 2012)
This book contains specialised information on the nutrition and training of the horse. Practical hints can be drawn from studies showing how apes indicate to us plants which have medicinal properties that can then be applied to equine treatment and also have an effect in nutraceuticals. Overviews are given on the potential of total mixed rations for the future of horse feeding and the practical feeding of obese horses and ponies. Nutrition considerations are given to avoid medical conditions. Methods used for performance diagnosis and training guidance of human athletes are applied here to equine management. In addition, training techniques which reduce the risk of back injury in the horse are explored and a review of the riders interaction with the horse is provided. Practical nutritional information acquired through research is applied to all aspects of managing endurance racehorses. Finally, expanded abstracts of original research are provided in very diverse fields of nutrition and training of horses. All those concerned with training, riding and feeding in the equine industry will benefit from the contents.